2004
DOI: 10.1128/jb.186.8.2328-2339.2004
|View full text |Cite
|
Sign up to set email alerts
|

A New Amidohydrolase from Bordetella or Alcaligenes Strain FB188 with Similarities to Histone Deacetylases

Abstract: The full-length gene encoding the histone deacetylase (HDAC)-like amidohydrolase (HDAH) from Bordetella or Alcaligenes (Bordetella/Alcaligenes) strain FB188 (DSM 11172) was cloned using degenerate primer PCR combined with inverse-PCR techniques and ultimately expressed in Escherichia coli. The expressed enzyme was biochemically characterized and found to be similar to the native enzyme for all properties examined. Nucleotide sequence analysis revealed an open reading frame of 1,110 bp which encodes a polypepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 30 publications
3
74
0
2
Order By: Relevance
“…This might be due to the general difficulty in defining catalytic properties of HDAC7 and other class IIa HDACs, since their biological substrates are unknown, and it has been shown that HDACs show different catalytic efficiencies with different substrate peptides (38,40,41,44). On the other hand, the fact that the side chain of His-843 points away from the cdHDAC7 active site could also explain the lower activity of cdHDAC7 since in this position His-843 is unlikely to contribute to the orientation of the substrate acetyl oxygen and the stabilization of the tetrahedral oxyanion intermediate during catalysis as proposed for the tyrosine of other HDACs.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the general difficulty in defining catalytic properties of HDAC7 and other class IIa HDACs, since their biological substrates are unknown, and it has been shown that HDACs show different catalytic efficiencies with different substrate peptides (38,40,41,44). On the other hand, the fact that the side chain of His-843 points away from the cdHDAC7 active site could also explain the lower activity of cdHDAC7 since in this position His-843 is unlikely to contribute to the orientation of the substrate acetyl oxygen and the stabilization of the tetrahedral oxyanion intermediate during catalysis as proposed for the tyrosine of other HDACs.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is supported by previous findings indicating a 100-fold weaker binding of inhibitors in the absence of the zinc ion. 17 At least in the case of CypX, a conformational flexibility of the ring moieties may also contribute to the less defined electron density. The two rings of Phe152 and Phe208, which line the active site channel, are in a co-planar orientation and could sandwich an inhibitor containing an aromatic ring system (Figure 1(c)).…”
Section: Inhibitor Complex Structuresmentioning
confidence: 99%
“…they process 3-N-trifluoroacetyl-lysine-containing substrates. 17,25 FB188 HDAH activity is blocked by common HDAC inhibitors containing a hydroxamate group like SAHA (suberoylanilide hydroxamic acid), and also by typical class 2 specific inhibitors such as 3-[4-(3-(3-chlorophenyl)-3-oxo-1-propen-1-yl)-1-methyl-1H-pyrrol-2-yl]-Nhydroxy-2-propen-amide (3c published by Mai et al; 26 see Table 1). Known class 1 specific inhibitors like HC-toxin and chlamydocin (both inhibitors are epoxyketones), that do not inhibit class 2 enzymes like HDAC6, 27,28 also do not inhibit FB188 HDAH (Table 1).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The measurement cycles are automated through a translation stage and a microscope camera. The enzyme HDAH can be produced easily in large quantities [9] and was chosen as a biochemical model because of its similarity to histone deacetylase (HDAC), a promising target in cancer therapy. The enzyme solution was diluted to 10 µg/ml and substrate solution to 83 µM using a weakly buffered solution of 500 µM BIS-TRIS propane, 100 µM citric acid, 1 mM NaCl, and 0.01 mg/ml bovine serum albumine at pH 8.6.…”
mentioning
confidence: 99%